Karya Puisi dan Biografi Penyair Indonesia-Papua dalam Dua Dekade (2000-2020): Poetry and Biography of Indonesian-Papua Poets in Two Decades (2000-2020) - Lestari, Ummu Fatimah Ria (Kibas Cenderawasih, 2023)
The development of the world of literature in the land of Papua in a period of 20 years has been quite dynamic. During this period, Indonesian-Papuan poets published their works on various themes. Documentation related to Indonesian-Papuan literary and literary works, especially the genre of poetry, is still minimal in Papua and in Indonesia more broadly. This is the background for conducting this research. Based on the background previously stated, this research will focus on poetry and biographies of Indonesian-Papuan poets in the past two decades (2000-2020). This study aims to inventory and discuss works and writers of Indonesian-Papuan poetry published in 2000-2020. This research was conducted using a description approach through literature study. In addition, secondary data collection was also carried out from various sources. This aims to obtain as much information as possible regarding the works of Indonesian-Papuan poets and poets over the past two decades (2000-2020). Most of the published works are packaged in poetry collection books. A total of 17 poetry collections have been presented by 14 Indonesian-Papuan poets in two decades.